Insights into the lemon (Citrus limon) epiphytic microbiome: impact of the biocontrol yeast Clavispora lusitaniae 146 - Rasuk, Maria Cecilia (2025)
Background: Postharvest lemons are affected by several fungal infections, and as alternatives to chemical fungicides for combating these infections, different microbial biocontrol agents have been studied, with the Clavispora lusitaniae 146 strain standing out. Although strain 146 has proven to be an effective agent, the influence of a microbial biological control agent on the postharvest lemon microbiome has not been studied until now. Thus, this study aimed to evaluate how the epiphytic microbiome of postharvest lemons is affected by the application of the biocontrol yeast C. lusitaniae 146. Results: In terms of bacterial composition, the most abundant genera were Sphingomonas, Pelomonas, and Bacillus and no significant differences in the composition were detected between the treated and control samples. Among fungi, Clavispora was predominant not only in the treated samples but also in the control, and statistics indicated differences, suggesting its significant role in modulating the epiphytic community composition of lemon. Understanding fruit microbiomes is vital for effective disease control, and this study provides insights into the microbial composition of the surface of lemon and the role of C. lusitaniae 146.